Prognostic impact of coronary microvascular dysfunction in patients with myocardial infarction evaluated by new angiography-derived index of microvascular resistance - Benoit Caullery; Laurent Riou; Stephanie Marliere; Estelle Vautrin; Nicolas Piliero; Olivier Ormerzzano; Helene Bouvaist; Gerald Vanzetto; Gilles Barone-Rochette (International Journal of Cardiology: Heart & Vasculature)
Background: Several methods for measuring IMR derived from angiography have been developed. AngioIMR is a novel method for the assessment of angiography-derived IMR with no requirement for a wire and hyperemia. The prognostic value of AngioIMR is unknown in STEMI patients. We aimed to provide the prognostic value of AngioIMR in patients with ST-elevation myocardial infarction (STEMI). Methods: This study included patients with STEMI who underwent invasive coronary angiography and primary percutaneous coronary intervention (PPCI). AngioIMR was calculated using computational flow and pressure simulation immediately after PPCI. The presence of significant coronary microvascular dysfunction was defined as AngioIMR > 40. The primary outcome was a composite of all cause death or hospitalization for heart failure (MACE). Results: A total of 178 patients were included (65.0 ± 12.8 years on average, 74 % male gender). An AngioIMR > 40 was found in 72 patients. During a median follow-up of 2.9 (2.3–6.9) years, a primary endpoint was observed in 56 patients. By Kaplan-Meier analysis, the risk of MACE was significantly higher in patients with AngioIMR > 40 (log-rank P < 0.01). An Angio IMR > 40 was significantly associated with the occurrence of the primary endpoint in univariate (70 % vs 27 %; hazard ratio 4.519; 95 % CI: 2.550–8.009; p < 0.0001) and multivariate analysis (Hazard ratio 4.282; 95 % CI: 2.325–7.886; p < 0.0001). AngioIMR model showed incremental prognostic value compared to a model with clinical and imaging risk predictors (C-index 0.84 vs 0.79; p = 0.04). Conlusion: Elevated AngioIMR showed a independent prognostic significance in STEMI patients. In addition to well-known risk factors, assessment of coronary microvascular dysfunction can be a feasible approach for early prevention and a therapeutic target in STEMI patients.